Analisis Pengaruh Profitabilitas, Likuiditas dan Struktur Modal Terhadap Nilai Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2014-2018 - Richard Richard (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This study examines the effect of profitability, liquidity and capital structure on firm value of banking companies listed in Indonesia Stock Exchange from 2014 until 2018. Samples of this study were 20 banking company. The method of analysis used in this research is regression analysis of data panel with Random Effect Model method. The result of this research show that profitability and capital structure partially have significant effect on firm value of banking company, while liquidity have no significant effect on firm value of banking company.